Performance improvement on spectral efficiency and peak to avearge power reduction for 5G system - Kavitha Thandapani; Ganesamoorthy Raju; Maniganda Pujali (Institute of Advanced Engineering and Science, 2022)
Filter bank multicarrier with offset quadrature amplitude modulation (FMBC/OQAM) system which can offer higher data rate 1 Gbps and improved bandwidth efficiency because of not require of cyclic prefix (CP) to avoid interference from the adjacent channels compared to fourth generation (4G) orthogonal frequency division multiplexing (OFDM) and other wireless systems. Because of these advantages FBMC/OQAM are used in fifth generation (5G) technology. In this FBMC/OQAM system, bandwidth capacity will be further increased by using multiple input multiple output (MIMO) channel. But in our proposed scheme we can use hyper–MIMO channel, in which at base station (BS) more number of transmitting antennas are used that for the improve the spectral efficiency performance better than traditional MIMO channel. But the most important drawback of hyper MIMO FBMC/OQAM is the higher peak to average-power ratio (PAPR) that degrade overall system performance in 5G. In 4G technology, to reduce PAPR a number of techniques are used. In our proposed system we can use mu-law non-linear companding technique and precoding discrete cosine transform (DCT) to reduce PAPR value for multicarrier modulation system compare to other systems.